Conceptual, Methodological, and Empirical Ambiguities in the Linkage Between Anger and Approach Comment on Carver and Harmon-Jones (2009). [article]. - Tomarken, Andrew J.
C.S. Carver and E. Harmon-Jones (2009) have made an important contribution to the understanding of anger, its linkage to higher order dimensions of emotion, and potential neurobiological substrates. The authors believe, however that their model and future research conducted to test it would be improved by a more precise explication and parsing of the primary constructs, a clearer articulation of the relation between anger and approach, and the use of methods for assessing brain activation that more precise than the electroencephalogram. Neuroimaging studies reviewed generally fail to corroborate several features of their model. -- (from the author)